Dissimilatory nitrate reduction to ammonium coupled to Fe(II) oxidation in sediments of a periodically hypoxic estuary. (28th October 2015) - Robertson, Elizabeth K.; Roberts, Keryn L.; Burdorf, Laurine D. W.; Cook, Perran; Thamdrup, Bo
Abstract: Estuarine sediments are critical for the remediation of large amounts of anthropogenic nitrogen (N) loading via production of N2 from nitrate by denitrification. However, nitrate is also recycled within sediments by dissimilatory nitrate reduction to ammonium (DNRA). Understanding the factors that influence the balance between denitrification and DNRA is thus crucial to constraining coastal N budgets. A potentially important factor is the availability of different electron donors (organic carbon, reduced iron and sulfur). Both denitrification and DNRA may be linked to ferrous iron oxidation, however the contribution of Fe(II)‐fueled nitrate reduction in natural environments is practically unknown. This study investigated how nitrate‐dependent Fe 2+ oxidation affects the partitioning between nitrate reduction pathways using 15 N‐tracing methods in sediments along the salinity gradient of the periodically hypoxic Yarra River estuary, Australia. Increased dissolved Fe 2+ availability resulted in significant enhancement of DNRA rates from around 10–20% total nitrate reduction in control incubations to over 40% in those with additional Fe 2+, at several sites. Increases in DNRA at some locations were accompanied by reductions in denitrification. Significant correlations were observed between Fe 2+ oxidation and DNRA rates, with reaction ratios corresponding to the stoichiometry of Fe 2+ ‐dependent DNRA. Our results provide experimental evidence for a direct coupling of DNRA to Fe 2+ oxidation across an estuarine gradient, suggesting that Fe 2+ availability may exert substantial control on the balance between retention and removal of bioavailable N. Thus, DNRA linked to Fe 2+ oxidation may be of general importance to environments with Fe‐rich sediments.